Effects of tacrolimus treatment on the gut microbiota and metabolites in liver transplant recipients - Guohui Wang; Lu Liu; Hanshu Zhang; Panpan Mao; Saijuan Lu; Xiaofang Zhang; Xingde Li; Cangsang Song (PLoS ONE, 2026)
Background Liver transplantation (LT) is an effective treatment for patients with end-stage liver disease. In recent years, more and more evidence has supported the association between gut microbiota dysbiosis and the pathogenesis and progression of liver diseases. Methods The study included 36 patients who received tacrolimus treatment after liver transplantation. Patients were stratified into subgroups according to three key variables: tacrolimus treatment duration, whole-blood tacrolimus concentration, and tacrolimus concentration-to-dose (C/D) ratio. Fecal samples and whole-blood specimens were collected from all participants. The Illumina HiSeq X platform was used to detect the gut metagenome, analyzing the composition and characteristics of the gut microbiota. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) technology was employed to detect metabolites of the gut microbiota, revealing their metabolic profiles. Results As the duration of tacrolimus use increased, the diversity of the gut microbiota also increased, and the abundance of Escherichia coli_D and Bacteroides stercoris rose. Additionally, the abundance of Brunovirus and Uetakevirus tended to decrease. The abundance of gene functions related to chemical carcinogenesis and bacterial invasion of epithelial cells significantly decreased. In the gut microbiota metabolites, 16 substances like Astragaloside A and Acetyl-L-carnitine significantly increased, while 108 substances like Capsaicin and TLK significantly decreased. Within a certain range, as the concentration of tacrolimus in whole blood increased, the diversity of the gut microbiota increased. The abundance of Phocaeicola and Klebsiella increased, and the abundance of Peduovirus among viruses also rose. However, excessively high concentrations may lead to a decrease in the diversity of the gut microbiota and a decrease in the abundance of Phocaeicola . With respect to the C/D ratio, increased ratios were linked to significantly higher levels of 57 fecal metabolites (e.g., PC 34:2, 5-Methyl-2’-deoxycytidine), whereas 13 metabolites (e.g., FAHFA 2:0/16:0) showed substantial declines. Conclusions Tacrolimus treatment is associated with distinct alterations in gut microbiota and metabolites among LT recipients. These findings provide a preliminary framework for future investigations aimed at optimizing immunosuppressive regimens, although their clinical translational potential requires validation in larger-scale, prospective cohort studies.